Navigating Academic Credentials in the Digital Age: Insights, Challenges, and Implications for Graduates - Khairuddin, Irni Eliana; Safian, Nurul Auni; Zaini, Muhamad Khairulnizam; Uzir, Nora’ayu Ahmad (Journal of Ecohumanism, 2024)
In the contemporary landscape of employment, managing academic credentials and experiential records is crucial for recent graduates. This study investigates the motivations, challenges, and technological approaches involved in this process. Drawing on the significance of credential records, the study examines practices in handling them and the technological adoption in their management. Through a qualitative methodology conducted from October to November 2023, involving five recent graduates aged 23-26, both online and physical interviews were conducted using phones and laptops, and data was analyzed using deductive coding in both English and Bahasa. The findings reveal various motivations driving individuals to manage their records, including peer influence, childhood awareness, program awareness, and social media exposure. However, challenges such as damage, misplacement, and security issues hinder effective management. Technological approaches such as backup emails, digital file protection, and platform improvements are proposed to address these challenges. This study contributes to understanding the complexities of academic record management and suggests practical solutions to enhance employability in the modern job market.